Fatty Acid-Derived Biofuels and Chemicals Production in Saccharomyces cerevisiae - Zhou, Yongjin J.; Buijs, Nicolaas A.; Siewers, Verena; Nielsen, Jens (Frontiers in Bioengineering and Biotechnology, 2014)
Volatile energy costs and environmental concerns have spurred interest in the development of alternative, renewable, sustainable and cost-effective energy resources. Advanced biofuels have potential to replace fossil fuels in supporting high-power demanding machinery such as aircrafts and trucks. Microbial biosynthesis is generally considered as an environmental friendly refinery process, and fatty acid biosynthesis is an attractive route to synthesize chemicals and especially drop-in biofuels due to the high degree of reduction of fatty acids. The robustness and excellent accessibility to molecular genetics make the yeast S. cerevisiae a suitable host for the production of biofuels, chemicals and pharmaceuticals, and recent advances in metabolic engineering as well as systems and synthetic biology allow us to engineer the yeast fatty acid metabolism and modification pathways for production of advanced biofuels and chemicals.